Focus on Form Approach in English Foreign Language Teaching - Seyyedi, Keivan; Aminzadeh, Sirvan; Omar, Jamal Ali (Zanco Journal of Human Sciences, 2024)
Numerous second language acquisition scholars assert that mere exposure to language is insufficient. They claim that activities that are only focused on message development are insufficient for developing a correct grasp of the language and urge a more form-centered approach to language instruction. ‘Focus on form’ (FonF) is a fundamental concept in task-based language teaching, originally introduced by Michael Long. It involves directing learners’ attention to the structures of language while they are actively engaged in tasks, as opposed to a structure-based approach called ‘focus on forms’ (FonFs), which focuses on explicit instruction of specific language forms. It maintains the significance of communicative language teaching principles, such as genuine communication and a student-centered approach. Understanding of this concept in second language acquisition (SLA) has experienced notable conversions. This article explores the evolution of Long’s original definition and reasons for reevaluation of teaching grammar. Then it presents a classification of different focus on form.